Effects of Green Innovations, Geopolitical Risk, Renewable Energy, and Urbanization on Environmental Quality in BRICS+T - Qamruzzaman, Md; Hossain, Mohammad Amzad; Hasan, Mohammad Tariq; Hossain, Ramisa Rutbata (International Journal of Energy Economics and Policy, 2025)
This research examines the interplay between green innovation, geopolitical risk, renewable energy consumption, and urbanization in influencing environmental quality across BRICS+T nations from 2004 to 2022. We utilized advanced panel estimation techniques in addressing slope heterogeneity, cross-sectional dependence, and long-run equilibrium dynamics in implementing DCE, DCE-IV, and DSUR. The findings indicate that green innovation and the use of renewable energy play a crucial role in improving environmental quality by lowering CO2 emissions and boosting the load capacity factor. Geopolitical risk and unplanned urbanization consistently undermine environmental outcomes, with both factors demonstrating statistically significant negative impacts across various models. Granger causality tests establish bidirectional relationships among geopolitical risk, urbanization, and environmental indicators, whereas green innovation and renewable energy exhibit a unidirectional influence. The results highlight the critical role of stable governance, the spread of technology, and cohesive urban planning in enhancing environmental conditions. The results underscore the necessity for unified national approaches spanning technological, political, and infrastructural areas. This research represents a pioneering effort to combine green innovation, geopolitical risk, renewable energy, and urbanization into a cohesive empirical framework centered on BRICS+T economies. This study reveals intricate interdependencies that are frequently neglected in the current environmental economics literature by utilizing strong long-run estimators and dual environmental proxies (CO2 and LCF). The study suggests that investments should be made in renewable energy infrastructure, alongside providing institutional support for green innovation, promoting sustainable urban planning, and fostering regional cooperation. These measures aim to reduce geopolitical volatility and maintain consistent environmental governance among BRICS+T nations.